Supply Chain Mapping to Prepare Golden Generation 2045 for Future Technology Infrastructure - Fernandes Andry Johanes; Nurprihatin Filscha; Liliana Lydia (E3S Web of Conferences, 2022)
The continued growth of the manufacturing industry as a result of shifting consumer demands has created turmoil in the supply chain process. The Indonesian government is currently focusing on human development and mastery of science and technology in the supply chain to prepare for Golden Generation 2045. Various problems arise in the current supply chain process, namely lack of transparency, complex production processes, and poor partner relations. The manufacturing industry must begin to prepare for the development of technology infrastructure, especially in supply chain integration, supply chain performance, and information sharing. Based on the problems experienced, a supply chain strategy mapping was carried out to identify challenges and improvements that needed to be made. The supply chain strategy is mapped with market trends and defines divisions affected by constructing new technology infrastructure. This strategy is taken into consideration in defining challenges and improving supply chain processes. This study aims to map supply chain strategies in the form of a mindmap to maximize processes and prepare technology infrastructure. Supply chain strategy mapping allows the manufacturing industry to implement strategies to react quickly if there are problems with suppliers, missing orders, spikes in demand, or other unexpected things.